2014
DOI: 10.1039/c4ra10539g
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and hypoglycemic efficacy of Poria cocos and Dioscorea opposita in prediabetes mellitus rats

Abstract: Poria cocos (Fu Ling) and Dioscorea opposita (Chinese Yam) were suggested to have potential benefits in blood sugar control. However, little is known about the underlying mechanisms. In this study, we investigated the anti-inflammatory and hypoglycemic effects of Poria cocos and Dioscorea opposita extracts in prediabetic rats. Fifty streptozotocin-injected rats with a mimic prediabetic status were gavaged with a single dose of either D. opposita (0.35 g kg À1 per day) or P. cocos (0.14 g kg À1 per day), a comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 51 publications
(68 reference statements)
0
13
0
Order By: Relevance
“…Yam (Dioscorea opposita) is an annual or perennial climbing plant. 1 The edible tubers of various species of Dioscorea 2 include many functional components, including mucin, allantoin, polysaccharides, avonoids, choline, and polyphenols, 3,4 which can reduce blood glucose, aid digestion, and relieve coughs. These components also exhibit anticoagulant, anti-cancer, and antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%
“…Yam (Dioscorea opposita) is an annual or perennial climbing plant. 1 The edible tubers of various species of Dioscorea 2 include many functional components, including mucin, allantoin, polysaccharides, avonoids, choline, and polyphenols, 3,4 which can reduce blood glucose, aid digestion, and relieve coughs. These components also exhibit anticoagulant, anti-cancer, and antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%
“…More than 80 triterpenoids have been isolated from PC to date [ 1 , 2 ]. Modern pharmacological research indicates that the triterpenoid acids in PCS, such as pachymic acid (PA), tumulosic acid (TUA), dehydrotumulosic acid (DTUA), poricoic acid A (PAA), poricoic acid B (PAB), polyporenic acid C (PAC), dehydrotrametenolic acid (DTRA), eburicoic acid (EA) and dehydroeburicoic acid (DEA), have a broad range of bioactivities including diuretic [ 3 , 4 ], anti-bacterial [ 5 , 6 ], anti-inflammatory [ 7 , 8 , 9 ], anti-oxidant [ 10 , 11 ], anti-tumor [ 12 , 13 , 14 ], anti-hyperglycemic [ 15 ], anti-emetic [ 16 ] and anti-rejection [ 17 ]. These triterpenoid acids are thus commonly regarded as the major bioactive components of PCS and are usually selected as chemical markers for the quality assessment of PCS [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Poria cocos (Schw.) Wolf is widely used in Yunnan, Guizhou, Hubei, Anhui, Fujian, Sichuan and Guangxi provinces in China, Modern medical research has indicated that P. cocos had comprehensive biological activities, such as antitumor [1,2,3,4,5,6,7,8,9,10,11], anti-inflammatory [12,13,14,15,16,17,18], immune-modulating [19,20], liver protecting [21,22] and so on, but particularly antitumor activity. Poria cocos (Schw.)…”
Section: Introductionmentioning
confidence: 99%